Do Infants in the First Year of Life Expect Equal Resource Allocations? - Buyukozer Dawkins, Melody; Sloane, Stephanie; Baillargeon, Renée (Frontiers in Psychology, 2019)
Recent research has provided converging evidence, using multiple tasks, of sensitivity to fairness in the second year of life. In contrast, findings in the first year have been mixed, leaving it unclear whether young infants possess an expectation of fairness. The present research examined the possibility that young infants might expect windfall resources to be divided equally between similar recipients, but might demonstrate this expectation only under very simple conditions. In three violation-of-expectation experiments, 9-month-olds (N = 120) expected an experimenter to divide two cookies equally between two animated puppets (1:1), and they detected a violation when she divided them unfairly instead (2:0). The same positive result was obtained whether the experimenter gave the cookies one by one to the puppets (Experiments 1–2) or first separated them onto placemats and then gave each puppet a placemat (Experiment 3). However, a negative result was obtained when four (as opposed to two) cookies were allocated: Infants looked about equally whether they saw a fair (2:2) or an unfair (3:1) distribution (Experiment 3). A final experiment revealed that 4-month-olds (N = 40) also expected an experimenter to distribute two cookies equally between two animated puppets (Experiment 4). Together, these and various control results support two broad conclusions. First, sensitivity to fairness emerges very early in life, consistent with claims that an abstract expectation of fairness is part of the basic structure of human moral cognition. Second, this expectation can at first be observed only under simple conditions, and speculations are offered as to why this might be the case.